The Role of Talent Management and Career Development in Improving Organizational Performance: A Study on the Indonesian Banking Industry - Achmad Darodjat, Tubagus (CV. Era Digital Nusantara, 2025)
This study explores the impact of talent management and career development on organizational performance within the Indonesian banking sector. The research addresses key challenges faced by banks, including talent retention, digital transformation, and regulatory adaptation. Using a qualitative case study approach, data were collected through semi-structured interviews and document analysis involving HR managers and senior employees from selected commercial banks. Thematic analysis was employed to extract patterns and insights. Findings reveal that structured talent management comprising competency-based recruitment, leadership training, and succession planning positively influences employee engagement and productivity. Similarly, clear career development pathways enhance employee retention and motivation. More importantly, the study highlights the synergistic effect when both strategies are implemented in tandem, leading to greater organizational agility and service quality. However, barriers such as cultural resistance and limited investment in HR systems persist. The study contributes to the strategic human resource management literature in emerging markets and offers practical recommendations for integrating human capital strategies with performance goals. It also identifies limitations related to sampling and scope, suggesting the need for broader and more inclusive future research.